Functional and internalizing disorders co-aggregate with cardiometabolic and immune-related diseases within families: a population-based cohort study - Olivier D. Steen; Martje Bos; Sonja L. van Ockenburg; Yiling Zhou; Ilja M. Nolte; Harold Snieder; Kenneth Kendler; Judith G. M. Rosmalen; Hanna M. van Loo (BMC Medicine)
Abstract Background Functional disorders share familial risk with internalizing disorders such as generalized anxiety disorder and depression, and are comorbid with cardiometabolic and immune-related diseases. We investigated whether functional and internalizing disorders co-aggregate with these diseases in families to gain insight into the aetiology of functional and internalizing disorders.  Methods We included 166,774 subjects (aged 3–94), from the population-based Lifelines Cohort Study, a Dutch general population cohort. We defined cases for three functional disorders (myalgic encephalomyelitis/chronic fatigue syndrome; ME/CFS, fibromyalgia, and irritable bowel syndrome; IBS), two internalizing disorders (major depressive disorder; MDD and generalized anxiety disorder; GAD), cardiometabolic diseases (obesity, metabolic associated steatotic liver disease, type 2 diabetes, hypertension and cardiovascular disease) and immune-related diseases (composite measures of auto-immune disease and atopy). We used logistic regression to model the prevalence of these disorders in the general population and in participants with affected relatives. Using these prevalence estimates, we assessed familial co-aggregation with (1) recurrence risk ratios (λ R ), and (2) familial correlations (r f ). Results All functional and internalizing disorders co-aggregated with immune-related diseases (λ R range 1.06–1.24). ME/CFS, FM, and MDD co-aggregated with most cardiometabolic diseases (λ R range 1.00–1.23). MDD, fibromyalgia, and ME/CFS showed similar familial correlation patterns with both disease groups (r f range 0.12–0.44), while patterns of IBS and GAD were more variable. Conclusions Internalizing and functional disorders share familial risk with immune-related and cardiometabolic diseases. This suggests that risk factors relevant to immune-related and cardiometabolic diseases may also be relevant for FDs. Future studies should investigate such risk factors to identify novel treatment targets.